2008
DOI: 10.4049/jimmunol.180.10.6675
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Mechanism of HIV-1 gp120 and Virion-Induced IL-1β Release in Primary Human Macrophages

Abstract: HIV-1 envelope glycoprotein gp120 induces, independently of infection, the release of proinflammatory cytokines, including IL-1β from macrophages, that are implicated in the pathogenesis of HIV-associated dementia. However, the signal transduction pathways involved have not been fully defined. Previously, our laboratory reported that soluble gp120 activates multiple protein kinases in primary human monocyte-derived macrophages, including the Src family kinase Lyn, PI3K, and the focal adhesion-related proline-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 76 publications
4
68
0
Order By: Relevance
“…Here, we have shown by several different techniques that there is a dramatic increase in Lyn kinase mRNA levels, suggesting that Lyn kinase is an enzyme with a potentially novel function that we observed in the THP-1 monocytes HCMV exposed to HCMV. These results are in agreement with a previous study conducted by Cheung and co-workers (Cheung et al, 2008), who have demonstrated that concomitant activation of Lyn kinase is required for HIV-1 envelope glycoprotein gp120-induced cytokine production in primary human monocyte-derived macrophages.…”
Section: Schematic Diagram Of Hypothesized Interrelationship Of Sr-a1supporting
confidence: 83%
“…Here, we have shown by several different techniques that there is a dramatic increase in Lyn kinase mRNA levels, suggesting that Lyn kinase is an enzyme with a potentially novel function that we observed in the THP-1 monocytes HCMV exposed to HCMV. These results are in agreement with a previous study conducted by Cheung and co-workers (Cheung et al, 2008), who have demonstrated that concomitant activation of Lyn kinase is required for HIV-1 envelope glycoprotein gp120-induced cytokine production in primary human monocyte-derived macrophages.…”
Section: Schematic Diagram Of Hypothesized Interrelationship Of Sr-a1supporting
confidence: 83%
“…Using the widely used method to prepare M2-MF (M-CSF derived) and M1-MF (GM-CSF derived) (13-16), we examined whether soluble Tat, gp120, or Nef differentially activated these MF by comparing the activation of MAPK, such as p38, JNK, and ERK. As reported (18)(19)(20)(21)(22)(23)(24)(25)(26)(27), all soluble HIV-1 proteins clearly activated p38 (Supplemental Fig. 1B).…”
Section: Resultsmentioning
confidence: 50%
“…Previous studies aimed at characterizing signal transduction pathways triggered by gp120 upon coreceptor engagement revealed that while some of them are activated by both gp120 and CCL4, others are uniquely triggered by gp120 (54)(55)(56)(57)(58)(59)(60). In this respect, it was reported that gp120, as well as CCL4, opened calcium-activated potassium-, chloride-, and calcium-permeant nonselective cation channels in macrophages.…”
Section: Discussionmentioning
confidence: 99%